(untitled) (gjstudies, 2017)
This research investigates the underexplored nexus between corporate financial leverageand the strategic selection of accounting policies, positing that leverage acts not merely asa financial metric but as a primary institutional force shaping reporting behavior. Movingbeyond traditional agency and contracting cost frameworks, we introduce a novel ’LeverageInduced Reporting Pressure’ (LIRP) model that conceptualizes debt covenants and creditorscrutiny as creating a distinct reporting environment characterized by asymmetric information pressures and outcome-dependent validation. The study employs a mixed-methodologyapproach, combining a longitudinal analysis of accounting policy changes in highly leveraged firms from 1995 to 2004 with a series of experimental simulations involving financialexecutives. Our findings reveal a non-linear relationship between leverage levels and accounting conservatism, with a critical threshold beyond which firms exhibit a pronounced shifttowards income-increasing and asset-valuing policies, contrary to the conservative bias predicted by debt covenant hypotheses. We identify a unique ’reporting elasticity’ phenomenon,where the sensitivity of accounting choices to earnings targets intensifies disproportionatelywith leverage. Furthermore, the research documents the emergence of ’covenant-proximatereporting’, a strategic clustering of aggressive accounting estimates in periods immediatelypreceding debt covenant tests. These results contribute a new theoretical lens for understanding financial reporting, suggesting that high leverage environments foster a calculativeculture where accounting policy becomes a direct tool for managing creditor perceptions andcovenant compliance, with significant implications for standard setters, auditors, and creditanalysts concerned with the quality and sustainability of reported earnings in debt-heavycapital structures.